Gender Representation of Osteoporosis in Patients with Urolithiasis - Bijelic, Radojka (Med Arch, 2015)
INTRODUCTION: A great number of clinical studies has indicated that the patients with calcium urolithiasis have a reduced mineral bone density. AIM: The aim of our research was to establish representation of osteoporosis, by measuring mineral bone density using the DEXA method, in patients with calcium urolithiasis, by gender. MATERIAL AND METHODS: The research was a prospective one, performed at the University Hospital of the Clinical Center of Banja Luka, at the Urology Clinic and Clinic for Endocrinology, Diabetes and Metabolic Diseases. The material in this research were the patients divided into two groups: a working group (the patients suffering from calcium urolithiasis) and a control group (the patients without calcium urolithiasis). One hundred and twenty (120) patients were included in both these groups, divided in three age subgroups: 20-40, 40-60 and over 60. The total working group consisted of 63 men (52.2%) and 57 (47.5%) women. In the control group, the number of women was 72 (60%) and 48 (40%) of men. Establishing of mineral bone density at L2-L4 of lumbal spine vertebrae and hip was done for the patients in both these groups, using DEXA method. RESULTS: Analysis of mineral bone density using DEXA method in patients by gender of working and control groups has shown that osteoporosis and osteopenia in patients of the working group is significantly more present in women (14% and 22.8%) compared to men (1.6% and 17.5%). When compared by gender in the control group, osteoporosis was present a lot more in women (36.1%) compared to men (2.1%). When observed for the total sample of both the working and control group, there was a statistically significant difference (p<0,01) related to gender structure, where the share of women with osteoporosis/osteopenia was significantly higher (36.1%) compared to men (4.2%). CONCLUSION: Representation of osteoporosis in women with urolithiasis, particularly of older age, is very expressed and this is why prevention measures should start as soon as possible, so as to avoid severe complications of this illness.